HUBUNGAN DAYA LEDAK OTOT TUNGKAI DAN KELENTUKAN PINGGANG DENGAN HASIL HEADING KEARAH GAWANG PADA TIM SSB RUMBAI JUNIOR U-14 PEKANBARU - Dicky Andesradika; Ramadi Ramadi; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abtract: The purpose of this study was to determine the relationship between leg muscle explosive power and waist flexion with the results of heading towards the goal on the SSB Rumbai Junior U - 14 Pekanbaru. This type of research conducted in this study is to use a correlational research design. The population in this study were 16 people, in this study researchers used a saturated sampling technique. Saturated sampling is a sampling technique when all members of the population are used as samples. From the results obtained there is a relationship of leg muscle explosive power and waist flexion with the results heading towards the goal on the SSB Rumbai Junior U - 14 Pekanbaru. Based on the analysis of the data obtained a correlation coefficient of r = 0.958 which was tested with Product Moment correlation analysis obtained rcount = 0.973 and rtable = 0.514 which means Rhitung (0.853)> Rtable (0.514) thus Ha is accepted at a significant level α = 0.05.Key Words: Explosive Power of Leg Muscles, Hip Flexibility, Course, Football